Alternative Splicing-Based Differences Between Hepatocellular Carcinoma and Intrahepatic Cholangiocarcinoma: Genes, Immune Microenvironment, and Survival Prognosis - Luo, Dingan; Zhao, Deze; Zhang, Mao; Hu, Chuan; Li, Haoran; Zhang, Shun; Chen, Xiaowu; Huttad, Lakshmi; Li, Bailiang; Jin, Cheng; Lin, Changwei; Han, Bing (Frontiers in Oncology, 2021)
Alternative splicing (AS) events is a novel biomarker of tumor tumorigenesis and progression. However, the comprehensive analysis of hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC) is lacking. Differentially expressed analysis was used to identify the differentially expressed alternative splicing (DEAS) events between HCC or ICC tissues and their normal tissues. The correlation between DEAS events and functional analyses or immune features was evaluated. The cluster analysis based on DEAS can accurately reflect the differences in the immune microenvironment between HCC and ICC. 45 immune checkpoints and 23 immune features were considered statistically significant in HCC, while only 7 immune checkpoints and 1 immune feature in ICC. Then, the prognostic value of DEAS events was studied and two transcripts with different basic cell functions (proliferation, cell cycle, invasion and migration) were produced by ADHFE1 through alternative splicing. Moreover, four nomograms were established in conjunction with relevant clinicopathological factors. Finally, we found two most significant splicing factors and further shown their protein crystal structure. The joint analysis of the AS events in HCC and ICC revealed novel insights into immune features and clinical prognosis, which might provide positive implications in HCC and ICC treatment.